Investigating climate resilience in Longyearbyen - Nurmi, Laura (UiT Norges arktiske universitet, 2021)
This thesis examines the adaptive capacity of Longyearbyen, in other words, how the community of Longyearbyen can foresee, prepare for and respond to climate-related challenges. I chose a case study methodology since my aim was to understand Longyearbyen as a living space, and how climate change is experienced across the environmental, economic, and social sectors. I used qualitative methods for data collection, where primary data comes from interviews and observations, supplemented by various secondary academic and non-academic sources. Based on a somewhat revised triangular model, the study examines resilience policies and plans in Svalbard, especially in the context of Longyearbyen. Derived from my findings, the key policies and plans addressing resilience include building emergency preparedness, emphasizing participatory methods, and developing climate-smart technologies while negotiating space for environmental protection. The locals are already involved in planning processes, but if more arenas for participation could be provided, their input could be increased, and thus more valuable knowledge would be available for political decision-making. There is also a strong, collective will to transform Longyearbyen from a former mining town into a modern research hub for sustainability.